‘Mijnheer Lochenberg’: on the construction of Khoesan as a criminal class - Blundell, Geoffrey; Ferreira, Angela; Meyers, Troy (Southern African Humanities, 2022)
Hans and Nicolaas Lochenberg are typically dismissed in a sentence as quintessential examples of 19th-century rogues living beyond the reach of the Cape and Natal colonies. The available archival data, however, show complex characters who deserve more nuanced and substantive treatment. Nicolaas, for example, was an aide and translator to the Gcaleka paramount, Hintsa, for almost 30 years. He partnered with Sarah, a Khoe woman, to raise some eight children, three of whom appear to have been Sarah’s children from previous relationships. Nicolaas played a significant role in establishing mission stations in 19th-century Xhosaland and in assisting shipwreck survivors. Two of his sons would go on to play prominent roles in the Eastern Cape. Willem, the elder, was a catechist for the Wesleyan Missionary Society while Hans, the younger, was an influential leader, with elements of the Mpondomise, Bhaca, and San communities in Nomansland acknowledging him as their chief. He was instrumental in orchestrating the legal defence of various communities accused of cattle rustling in Nomansland and he assisted colonial travellers and explorers. With enough archival evidence to offer a contrapposto, it is necessary to consider why Hans and Nicolaas are persistently dismissed as criminal exemplars.